2017
DOI: 10.1007/s00296-017-3888-x
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte chemoattractant protein-1 as a marker of systemic lupus erythematosus: an observational study

Abstract: There is a pivotal need for new markers to be tested in every day clinical practice for systemic lupus erythematosus (SLE) and lupus nephritis (LN). The levels of monocyte chemoattractant protein-1 (MCP-1) in the serum and urine of 72 SLE patients (27 with LN and 45 without LN involvement) and 30 healthy individuals were studied to establish their clinical significance. The SLE Disease Activity Index (SLEDAI) was used to establish the disease activity. Urine and serum MCP-1 was determined using the sandwich en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 33 publications
6
9
0
Order By: Relevance
“…Increasing MCP-1 increased VT and MCS, which contradicts the data on the disease activity in SLE, where the serum, cerebrospinal and urinary MCP-1 levels were increased with disease exacerbation; and MCP-1 was also shown to be associated with fatigue and depression in SLE; while simultaneously beingnegatively associated with all SF-36 items, (all, p < 0.01) [4]. Our results were similar to other studies which showed that the MCP-1 levels remain elevated after a long-term immunosuppression, even when the disease activity had subsided [44,45,46]. More generally, MCP-1 levels have been shown to be equivalent between women with and without Exhaustion Disorders, anxiety or depression [47]; and MCP-1 is important for combating bacterial infections [48].…”
Section: Discussionsupporting
confidence: 89%
“…Increasing MCP-1 increased VT and MCS, which contradicts the data on the disease activity in SLE, where the serum, cerebrospinal and urinary MCP-1 levels were increased with disease exacerbation; and MCP-1 was also shown to be associated with fatigue and depression in SLE; while simultaneously beingnegatively associated with all SF-36 items, (all, p < 0.01) [4]. Our results were similar to other studies which showed that the MCP-1 levels remain elevated after a long-term immunosuppression, even when the disease activity had subsided [44,45,46]. More generally, MCP-1 levels have been shown to be equivalent between women with and without Exhaustion Disorders, anxiety or depression [47]; and MCP-1 is important for combating bacterial infections [48].…”
Section: Discussionsupporting
confidence: 89%
“…Despite the inconsistent results, these proinflammatory cytokines/chemokines have emerged as candidate biomarkers to show disease activity. 1019 Only a handful of studies have involved patients without SLE. 10,16,20…”
Section: Introductionmentioning
confidence: 99%
“…Even if it is produced by many cell types, it is mainly expressed by activated monocytes/macrophages, T cells, and natural killer cells and takes part in leukocyte infiltration to the kidney [26]. This and the observation that its antagonist can ameliorate the induction and progression of LN in transgenic mouse model [27], make it one of the most used biomarkers when considering LN. As shown in online suppl.…”
Section: Resultsmentioning
confidence: 99%